Gynecological problems of married women in the reproductive age group of urban Belgaum, Karnataka - S. Poornima; S.M. Katti; M.D. Mallapur; M. Vinay (Al Ameen Medical College, 2013)
Background: Gynecological problems are universal in occurrence, however, the prevalence, awareness and treatment seeking for these problems varies from region to region. In Indian scenario the women are faced with social and economic barriers in seeking care. In order to understand the gynecological problems of women in our newly adapted urban field practice area this study was undertaken. Objective: To determine the prevalence of gynecological problems among the married women of the reproductive age group in urban area of Belgaum city. Methodology: 400 married women were interviewed using a pre-tested, pre-designed, semi structured questionnaire. The participants were subjected to medical examination by a qualified gynecologist and subjected to lab investigations as required. Results: 282 (70.50 %) women had reproductive tract infections, 83 (20.75%) had menstrual problems, 108 (27.00%) had UTIs, 97 (24.25 %) had chronic and 77(19.25%) had acute pelvic inflammatory disease. The total prevalence of gynecological problems per woman was 1.51. There was no significant association of prevalence of gynecological problems and the age, education and socio-economic status. The overall treatment seeking behavior was 15.72%. Treatment seeking was highest for conceiving difficulty (48.14 %) and least for RTIs (9.57 %). Conclusion: There is high prevalence of gynecological problems among the urban married women of Belgaum city.